PERAN PENYULUHAN DALAM PEMBERDAYAAN PETANI KELAPA POLA SWADAYA DI DESA SUNGAI LOKAN KECAMATAN ENOK KABUPATEN INDRAGIRI HILIR - Ali Sabar; Roza Yulida; Kausar ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This research aims to: (1) know the description of counseling in Sungai Lokan;(2)Analyzing the level of counseling role and the level of empoweringself-help system of coconut farmersin Sungai Lokan (3) Analyzing the relationship of the counselor’srole toward empowering self-help system of coconut farmersin Sungai Lokan. This research was conducted in Sungai Lokan of Indragiri Hilir sub-district of Enoch Regency.In this study as many as 30 farmers have taken as samples of 166 populations and selected by purposeful sampling and then were interviewed as respondents. Validity and reliability analysis have been done as a measuring instrument to the 30 respondents.To answering the first goal was done by qualitative descriptive analysis that used to determine a general overview of counseling in Sungai Lokan. To answer the second goal, then the Likert Scale Analysis was used to analyze the level of the role of counselor and empowerment of self-help system farmers in Sungai Lokan. To answering third goal, then the Spearman Rank Correlation Analysis was used to analyze the role of counselor relationship to the empowerment of self-help system coconut farmers.The result of indicate: (1) the counseling role was “less a role” in self-help system of coconut farming activities, which consists of a counselor’s role as an educational counselor. (2) Counseling has not quite well in empowering self-help system of coconut farmers, which consist of human resources, the productive and institutional economy. (3) The relationship to empowerment counseling role of an self-help system that there were no significant level of the relationship. Keywords: Counseling Role, Empowerment, Coconut Farmers, Self-help system